SURPLUS ARISING THROUGH REVALUATION. - Martin, O. R. (The Accounting Review, 1927)
That fixed assets should appear in the accounts on the basis of their original cost, adjusted only for depredation, has been a much revered canon of accounting, and much has been written and many considerations urged in support of this rule. Among the affirmative arguments should be mentioned the following: 1) original cost represents the value of such assets to the enterprise as a going concern; 2) writing up the value of fixed assets necessitates a corresponding credit to surplus and such credit constitutes an unrealized profit; 3) changing values of fixed assets are due in a large measure to the changing value of the monetary unit and it is both unwise and impractical to attempt to use the dollar as a unit of measure and at the same time endeavor to allow for the fluctuations in its purchasing power; 4) accounting is fundamentally a system of recording logically the historical facts of a business enterprise and this record will be most accurate and trustworthy if there be strict adherence to actual financial transactions and no attempt made to incorporate into the accounting structure the hypotheses and postulates of economic analysis or the dictates of individual judgment; 5) the practical difficulties inherent in the task of measuring current economic values are such as to invalidate the use of accounting as an effective instrument of business control.